A preliminary study on FDM prototype surface roughness - Khan, Shah Fenner; Salleh, Ahmad Faizal; Sharif, Safian; Mohamad, Zulkepli; A. Rashid, Zulkifli; Murad, Muhamad Nasir (2006)
Rapid prototyping (RP) is often used to describe the technologies that are used to fabricate physical objects directly from 3D CAD model. And sometime is also known as Solid Freeform Fabrication (SFF). These methods are generally similar to each other in that they add and bond materials in layer wise fashion to form 3 dimensional objects. Processes such as stereolithography (SLA), selective laser sintering (SLS), fused deposition modeling (FDM), layered object modeling (LOM) and 3D Printing (3DP) are part of this technology. This project study the effect of slice thickness and support parameters on the Water Soluble System, Fused Deposition Modeling (FDM) product quality in terms of surface roughness produced during part building. The results obtained show that slice thickness and support parameters influence the studied responses. The thickness of the support structures has affected the surface roughness obtained.